2016
DOI: 10.1016/j.cognition.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Strength and weight: The determinants of choice and confidence

Abstract: Evidence for different hypotheses is often treated as a singular construct, but it can be dissociated into two parts: its strength, the proportion of pieces of information favoring one hypothesis; and its weight, the total number of pieces of information available. However, cognitive and neural models of evidence accumulation often make a proportional representation assumption, implying that people take these two factors into account equally when making their decisions and judgments. We examine this assumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 53 publications
6
47
1
Order By: Relevance
“…The present study exploited a previously observed effect of evidence variability to dissociate objective accuracy from subjective confidence, without specifically aiming to understand the cause of this dissociation. Nonetheless, in replicating previous findings using the same paradigm (Boldt et al, 2017) and related manipulations (Spence et al, 2015), our results stand in apparent contrast to recent findings that evidence mean more strongly influences choice and confidence than evidence weight (Kvam & Pleskac, 2016). In that study, however, evidence weight was operationalized as the amount of evidence, as distinct from the variability of presented evidence studied here.…”
Section: Models Of Decision Making and Confidencesupporting
confidence: 76%
“…The present study exploited a previously observed effect of evidence variability to dissociate objective accuracy from subjective confidence, without specifically aiming to understand the cause of this dissociation. Nonetheless, in replicating previous findings using the same paradigm (Boldt et al, 2017) and related manipulations (Spence et al, 2015), our results stand in apparent contrast to recent findings that evidence mean more strongly influences choice and confidence than evidence weight (Kvam & Pleskac, 2016). In that study, however, evidence weight was operationalized as the amount of evidence, as distinct from the variability of presented evidence studied here.…”
Section: Models Of Decision Making and Confidencesupporting
confidence: 76%
“…Median splits were used because the psychological scaling of these quantities is unlikely to be linear. These scaling issues, which are topics of investigation in their own right (Siegler and Opfer, 2003; Kvam and Pleskac, 2016), are beyond the scope of this contribution.…”
Section: Resultsmentioning
confidence: 99%
“…These include both the simple random walk models, where a decision maker has a discrete set of states (e.g., 11 confidence levels, 0/10/20/.../100) that they move through over time, shown in Figure 2, and the more common diffusion models where the "states" are a continuously-valued level of evidence (such as 0-100, including all numbers in between). Since the discrete-state random walks approach a diffusion process as the number of states gets very large, we group these two approaches together under the umbrella of Markov process, which have been used to model choices and response times (Emerson, 1970;Luce, 1986;Stone, 1960) as well as probability judgments (Edwards et al, 1963;Wald & Wolfowitz, 1949, 1948Kvam & Pleskac, 2016;Moran et al, 2015;Ratcliff & Starns, 2009;Yu et al, 2015) in domains such as memory (Ratcliff, 1978), categorization (Nosofsky & Palmeri, 1997), and inference (Pleskac & Busemeyer, 2010).…”
Section: Markov and Quantum Views Of Evidence Accumulationmentioning
confidence: 99%